Te-based composite positive electrode material, preparation method thereof and application of Te-based composite positive electrode material in aqueous zinc ion battery
By etching activated carbon in aqueous zinc ion batteries with alkali activators, the composite material of porous carbon carrier and Te was prepared, which solved the problems of low Te utilization rate and large volume expansion in zinc ion batteries, and achieved high rate performance and cycle stability , promotes the commercial application of zinc ion batteries.
Patent Information
- Application Number
- CN202411688809.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-07
AI Technical Summary
The commercialization of aqueous zinc ion batteries is hindered because the rate performance and cycle life of existing cathode materials are insufficient, mainly due to the electrostatic repulsion between zinc ions and Te, which leads to low utilization rate and large volume expansion.
The porous carbon carrier is prepared by etching the activated carbon with alkali activator, and the second heat treatment is performed with Te to form a Te-based composite positive electrode material. By increasing the electrode conductivity and pore structure, the diffusion and transmission efficiency of zinc ions are improved and the volume expansion of Te is reduced. .
It significantly improves the rate performance and cycling performance of aqueous zinc ion batteries, ensures high specific capacity and stability, overcomes the problems of insufficient conductivity and energy storage performance of existing cathode materials, and has good application prospects.
Smart Images

Figure CN119275384A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zinc ion batteries, and in particular to a Te-based composite positive electrode material and a preparation method thereof and application thereof in aqueous zinc ion batteries. Background Art
[0002] Among all available energy storage batteries today, aqueous zinc-ion batteries have intrinsic safety, excellent theoretical capacity, and low redox potential. However, the commercialization of aqueous zinc-ion batteries is hampered by the lack of cathode materials with satisfactory rate performance and cycle life. In the past few years, various cathode materials have been developed, including manganese-based compounds, vanadium-based oxides, and Prussian blue analogs, but the significant electrostatic repulsion between zinc ions and the host leads to poor specific capacity and cycle life of these ion-intercalated cathode materials, which greatly limits their practical application in aqueous zinc-ion batteries.
[0003] Tellurium (Te) has high electronic conductivity and volume capacity and is a promising high-performance cathode material for aqueous zinc-ion batteries. However, its low utilization rate and large volume expansion result in insufficient rate performance and cycle performance, which hinders its practical application. Summary of the invention
[0004] The object of the present invention is to provide a Te-based composite positive electrode material and a preparation method thereof and application in an aqueous zinc ion battery, so as to inhibit the volume expansion of Te and improve its utilization rate, thereby improving the rate performance and cycle performance of the aqueous zinc ion battery.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a Te-based composite positive electrode material, comprising the following steps:
[0007] mixing an alkali activator, activated carbon and water, and subjecting the resulting mixture to a first heat treatment to obtain a heat-treated product;
[0008] The heat-treated product is mixed with an acid solution and etched to obtain a porous carbon support;
[0009] The porous carbon support is ground and mixed with Te, and a second heat treatment is performed to obtain a Te-based composite positive electrode material.
[0010] Preferably, the alkali activator includes one or more of KOH, NaOH, KHCO3, NaHCO3 and K2CO3.
[0011] Preferably, the mass ratio of the activated carbon to the alkali activator is 1:1-3.
[0012] Preferably, the alkali activator, activated carbon and water are mixed for 6 to 12 hours.
[0013] Preferably, the temperature of the first heat treatment is 600-800° C., the time is 1-5 hours, and the treatment atmosphere is N 2 .
[0014] Preferably, the acid solution includes a hydrochloric acid solution, and the concentration of the acid solution is 1 to 5 mol / L; the etching time is 3 to 12 hours.
[0015] Preferably, the mass ratio of the porous carbon support to Te is 0.5-3:1; the temperature of the second heat treatment is 450-650°C, the time is 3-15h, and the atmosphere is N2 atmosphere.
[0016] The present invention provides a Te-based composite positive electrode material prepared by the preparation method described in the above technical solution, comprising a porous carbon carrier and Te particles loaded on the porous carbon carrier.
[0017] Preferably, the porous carbon carrier is in an irregular block shape with an average thickness of 40 μm and a length of 70 μm; the loading amount of Te particles on the porous carbon carrier is 0.5-3 mg / cm 2 .
[0018] The present invention provides the application of a Te-based composite positive electrode material prepared by the preparation method described in the above technical solution in an aqueous zinc ion battery.
[0019] The present invention provides a method for preparing a Te-based composite positive electrode material. The porous carbon carrier prepared by etching activated carbon with an alkaline activator can increase the conductivity of the electrode, help improve the conductivity and electron transfer rate of the battery, and thus improve the performance of the battery. The porous carbon carrier surface has a large number of pore structures, which can increase the specific surface area of the electrode, increase the contact area between zinc ions and the electrode material, and help improve the energy density and power density of the battery. In addition, manufacturing defects on the surface of the material and introducing a large number of polar oxygen-containing functional groups are conducive to improving the adsorption of Te by the porous carbon, so that Te is chemically adsorbed on the micropores of the porous carbon, thereby reducing the volume expansion of Te during the cycle and effectively increasing the loading amount of Te on the porous carbon carrier. The highly porous structure provides a good diffusion channel, which is conducive to the rapid diffusion and migration of zinc ions during the charge and discharge process, and realizes rapid ion transmission, thereby improving the charge and discharge rate, specific capacity, cycle performance and rate performance of the zinc ion battery, and has good application prospects in the field of zinc ion battery production and manufacturing.
[0020] The present invention adopts a porous carbon carrier to load Te, which not only maintains the stability of the structure, but also provides abundant electrochemical active sites and efficient charge transfer channels, thereby providing space for zinc ions to be deintercalated, and can better play the advantages of high specific capacity of tellurium-based positive electrode materials. The energy density is not negatively affected by the easy collapse of the tellurium-based material lattice, which is conducive to the utilization of Te. The positive electrode material is used in zinc ion batteries to show sufficient specific capacity, high rate performance and reliable cycle stability, overcomes the deficiencies of existing aqueous zinc ion battery positive electrode materials in terms of conductivity and energy storage performance, solves the limitation problems caused by the positive electrode materials on battery energy density, specific capacity and cycle stability, and has practical application value.
[0021] The present invention adopts KOH to etch commercial activated carbon to prepare the porous carbon carrier. The commercial activated carbon is cheap, and the method is simple and low in cost.
[0022] The Te-based composite positive electrode material prepared by the present invention has high energy density and stability. This is because alkali-activated porous carbon is used as a carrier, defects and a large number of oxygen-containing polar functional groups are introduced, and the porous carbon carrier has a large number of micropores on its surface, which is conducive to the adsorption and confinement of Te and polytellurides (ZnTe and ZnTe2 generated during the charge and discharge state of the material) in the micropores, preventing them from falling off from the carbon carrier due to volume expansion during the reaction process, thereby avoiding the loss of positive electrode active materials during the cycle.
[0023] The Te-based composite cathode material prepared by the present invention exhibits high specific capacity, excellent cycle performance and rate performance in aqueous zinc ion batteries. -1 At a current density of 2.5 MW, it still has a capacity of 225.9 mAh g after 1000 cycles. -1 reversible specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the KOH-C material prepared in Example 1;
[0025] Figure 2 is a scanning electron microscope image of the raw material Te in Example 1;
[0026] Figure 3 This is an energy dispersive X-ray spectrum of the KOH-C / Te material prepared in Example 1;
[0027] Figure 4 The KOH-C / Te material prepared in Example 1 and the materials in Comparative Examples 1 to 2 were prepared at 0.1Ag. -1 Constant current charge and discharge curves under current density;
[0028] Figure 5The cyclic voltammetry curves of the KOH-C / Te material prepared in Example 1 at different scan rates;
[0029] Figure 6 The KOH-C / Te material prepared in Example 1 was heated to 0.1 Ag. -1 Constant current intermittent titration curve under current density and Zn in the charge and discharge process 2+ Diffusion coefficient.
[0030] Figure 7 The KOH-C / Te material prepared in Example 1 and the materials in Comparative Examples 1 to 2 were prepared at 1Ag. -1 Plot of long cycles at different current densities. DETAILED DESCRIPTION
[0031] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0032] The present invention provides a method for preparing a Te-based composite positive electrode material, comprising the following steps:
[0033] mixing an alkali activator, activated carbon and water, and subjecting the resulting mixture to a first heat treatment to obtain a heat-treated product;
[0034] The heat-treated product is mixed with an acid solution and etched to obtain a porous carbon support;
[0035] The porous carbon support is ground and mixed with Te, and a second heat treatment is performed to obtain a Te-based composite positive electrode material.
[0036] The invention mixes an alkali activator, activated carbon and water, and performs a first heat treatment on the obtained mixture to obtain a heat-treated product.
[0037] In the present invention, the alkaline activator preferably includes one or more of KOH, NaOH, KHCO3, NaHCO3 and K2CO3; when the alkaline activator is two or more of the above, the present invention has no special limitation on the ratio of different types of alkaline activators, and any ratio is acceptable; the activated carbon is preferably commercial activated carbon.
[0038] In the present invention, the mass ratio of the activated carbon to the alkali activator is preferably 1:1 to 3, more preferably 1:2 to 3. The present invention has no particular limitation on the amount of water, as long as the materials are mixed evenly.
[0039] In the present invention, the mixing time of the alkali activator, activated carbon and water is preferably 6 to 12 hours, more preferably 8 to 12 hours.
[0040] The present invention preferably dissolves the alkaline activator in water, adds activated carbon, and after ultrasonication for 30 minutes, stirs and mixes, and dries in a drying oven at 80° C. to obtain activated carbon with the alkaline activator on the surface, and performs a first heat treatment.
[0041] In the present invention, the temperature of the first heat treatment is preferably 600-800°C, more preferably 700-750°C, the time is preferably 1-5h, more preferably 2-3h, and the treatment atmosphere is preferably N2.
[0042] The present invention improves the defects (oxygen vacancies) of the porous carbon carrier by activation and introduces a large number of polar functional groups (CO bonds), thereby improving the chemical adsorption of Te by the porous carbon, thereby subsequently achieving the combination of Te and the porous carbon.
[0043] In the present invention, the oxygen vacancies and CO bonds formed on the porous carbon support after alkali activation are the key factors to improve its electrochemical performance. These polar defects or functional groups can promote the surface chemical adsorption of electrolyte ions and improve the composite material's Zn 2+ The adsorption energy of the composite material is reduced 2+ The migration barrier of Te can improve the charge transfer kinetics and structural stability of the composite material. In addition, Te can be effectively bound in the micropores of the porous carbon support during the reaction, preventing it from falling off from the carbon support due to volume expansion during the reaction, thus avoiding the loss of positive electrode active materials during the cycle.
[0044] After obtaining the heat-treated product, the present invention mixes the heat-treated product with an acid solution and performs etching to obtain a porous carbon carrier.
[0045] In the present invention, the acid solution preferably includes a hydrochloric acid solution, and the concentration of the acid solution is preferably 1 to 5 mol / L, more preferably 2 to 3 mol / L; the etching time is preferably 3 to 12 h, more preferably 6 to 8 h.
[0046] After the etching is completed, the present invention preferably washes the obtained product with deionized water and dries it at 60° C. to obtain a porous carbon carrier.
[0047] After obtaining the porous carbon support, the present invention grinds and mixes the porous carbon support with Te, and performs a second heat treatment to obtain a Te-based composite positive electrode material.
[0048] The Te used in the present invention is preferably Te particles in the form of irregular blocks with an average particle size of 30 μm.
[0049] In the present invention, the mass ratio of the porous carbon support to Te is preferably 0.5 to 3:1, more preferably 1 to 2:1, and further preferably 1:1; the grinding and mixing time is preferably 1 h.
[0050] In the present invention, the temperature of the second heat treatment is preferably 450-650°C, more preferably 550-600°C, the time is preferably 3-15h, more preferably 8-12h, and the atmosphere is preferably N2 atmosphere.
[0051] The present invention physically mixes the porous carbon carrier and Te by grinding and mixing, grinds so that Te is fully in contact with the surface of the porous carbon carrier, and then deposits Te on the porous carbon surface through vapor phase by heat treatment.
[0052] The present invention provides a Te-based composite positive electrode material prepared by the preparation method described in the above technical solution, comprising a porous carbon carrier and Te particles loaded on the porous carbon carrier.
[0053] In the present invention, the porous carbon carrier is in an irregular block shape with an average thickness of 40 μm and a length of 70 μm; the loading amount of Te particles on the porous carbon carrier is preferably 0.5 to 3 mg / cm 2 , more preferably 0.9 to 2 mg / cm 2 , more preferably 1.8 to 2 mg / cm 2 .
[0054] The present invention provides the application of the Te-based composite positive electrode material prepared by the preparation method described in the above technical solution in an aqueous zinc ion battery. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.
[0055] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] Example 1
[0057] (1) Dissolve 3 g of KOH in 20 mL of deionized water, add 1 g of commercial activated carbon, sonicate for 30 min, and stir for 12 h to obtain a mixed solution;
[0058] (2) transferring the mixed solution obtained in step (1) into a culture dish and drying it in a forced air drying oven at 80° C. to obtain activated carbon having KOH on its surface;
[0059] (3) annealing the product obtained in step (2) in a tube furnace under a N2 atmosphere at a temperature of 800°C for 3 hours, and then naturally cooling to room temperature;
[0060] (4) The product obtained in step (3) was placed in a 2 mol / L dilute hydrochloric acid solution and etched for 6 h, then washed with deionized water, and dried in a forced air drying oven at 60° C. to obtain KOH-C;
[0061] (5) Grind 1 g of KOH-C and 1 g of Te in a mortar for 1 h;
[0062] (6) The mixture obtained in step (5) was transferred into a tube furnace for annealing treatment under N2 atmosphere at a temperature of 550°C for 12 h, and then naturally cooled to room temperature to obtain a KOH-C / Te positive electrode material. The loading amount of Te particles on the porous carbon carrier was 2 mg / cm 2 .
[0063] Example 2
[0064] (1) Dissolve 2 g of KOH in 20 mL of deionized water, add 1 g of commercial activated carbon, sonicate for 30 min, and stir for 6 h to obtain a mixed solution;
[0065] (2) transferring the mixed solution obtained in step (1) into a culture dish and drying it in a forced air drying oven at 80° C. to obtain activated carbon having KOH on its surface;
[0066] (3) subjecting the product obtained in step (2) to high temperature annealing in a tube furnace under a N2 atmosphere at a temperature of 700°C for 2 h;
[0067] (4) The product obtained in step (3) was placed in a 2 mol / L dilute hydrochloric acid solution and etched for 6 h, then washed with deionized water, and dried in a forced air drying oven at 60° C. to obtain KOH-C;
[0068] (5) Grind 1 g KOH-C and 2 g Te in a mortar for 1 h;
[0069] (6) The mixture obtained in step (5) was transferred into a tube furnace for high temperature annealing treatment. The annealing temperature was 550°C for 12 h under N2 atmosphere, and then naturally cooled to room temperature to obtain a KOH-C / Te electrode material. The loading amount of Te particles on the porous carbon support was 1.8 mg / cm 2 .
[0070] Example 3
[0071] (1) Dissolve 1 g of KOH in 20 mL of deionized water, add 1 g of commercial activated carbon, sonicate for 30 min, and stir for 8 h to obtain a mixed solution;
[0072] (2) transferring the mixed solution obtained in step (1) into a culture dish and drying it in a forced air drying oven at 80° C. to obtain activated carbon having KOH on its surface;
[0073] (3) subjecting the product obtained in step (2) to high temperature annealing in a tube furnace under a N2 atmosphere at a temperature of 600°C for a time of 1 h;
[0074] (4) The product obtained in step (3) was placed in a 2 mol / L dilute hydrochloric acid solution and etched for 3 h, then washed with deionized water, and dried in a forced air drying oven at 60° C. to obtain KOH-C;
[0075] (5) Grind 2 g KOH-C and 1 g Te in a mortar for 1 h;
[0076] (6) The mixture obtained in step (5) was transferred into a tube furnace for high temperature annealing treatment. The annealing temperature was 550°C for 12 h under N2 atmosphere, and then naturally cooled to room temperature to obtain a KOH-C / Te electrode material. The loading amount of Te particles on the porous carbon support was 1.2 mg / cm 2 .
[0077] Example 4
[0078] (1) Dissolve 3 g of KOH in 20 mL of deionized water, add 1 g of commercial activated carbon, sonicate for 30 min, and stir for 8 h to obtain a mixed solution;
[0079] (2) transferring the mixed solution obtained in step (1) into a culture dish and drying it in a forced air drying oven at 80° C. to obtain activated carbon having KOH on its surface;
[0080] (3) subjecting the product obtained in step (2) to high temperature annealing in a tube furnace under a N2 atmosphere at a temperature of 800°C for 5 hours;
[0081] (4) The product obtained in step (3) was placed in a 2 mol / L dilute hydrochloric acid solution and etched for 12 h, then washed with deionized water, and dried in a forced air drying oven at 60° C. to obtain KOH-C;
[0082] (5) 3 g KOH-C and 1 g Te were ground and mixed in a mortar for 1 h;
[0083] (6) The mixture obtained in step (5) was transferred into a tube furnace for high temperature annealing treatment. Under N2 atmosphere, the annealing temperature was 550°C for 12 h, and the mixture was naturally cooled to room temperature to obtain a KOH-C / Te electrode material. The loading amount of Te particles on the porous carbon support was 0.9 mg / cm 2 .
[0084] Comparative Example 1
[0085] Take Te as comparative example 1, and record it as Pure Te.
[0086] Comparative Example 2
[0087] (1) 1 g of KOH and 1 g of Te were ground and mixed in a mortar for 1 h;
[0088] (2) The mixture obtained in step (1) was transferred into a tube furnace for annealing treatment under N2 atmosphere at a temperature of 550°C for 12 h, and then naturally cooled to room temperature to obtain a C / Te positive electrode material (denoted as Pure C / Te). The loading amount of Te particles on the porous carbon support was 0.9 mg / cm 2 .
[0089] Test Example 1
[0090] Figure 1 This is a scanning electron microscope image of the KOH-C material prepared in Example 1. It is observed that the KOH-C is in an irregular block shape with a rough surface; the average thickness is 40 μm and the length is 70 μm.
[0091] Figure 2 This is a scanning electron microscope image of the raw material Te in Example 1; it was observed that the Te particles were irregular blocks with an average particle size of 30 μm.
[0092] Figure 3 This is an energy dispersive X-ray spectrum of the KOH-C / Te material prepared in Example 1. It is observed that Te is uniformly loaded on KOH-C.
[0093] Test Example 2
[0094] The KOH-C / Te material prepared in Example 1 was used as the positive electrode and zinc foil as the negative electrode. Electrochemical tests were carried out in a 2 mol / L ZnSO4 electrolyte. The test results are shown in FIG. Figures 4 to 7 shown.
[0095] Figure 4 The KOH-C / Te material prepared in Example 1 and the materials in Comparative Examples 1 to 2 were prepared at 0.1Ag. -1 The constant current charge and discharge curve under current density is given by Figure 4 It can be seen that the discharge capacity reaches 481.75 mAh g in the voltage window of 0.1 V-1.8 V. -1 , the specific capacity is better than Te and C / Te.
[0096] Figure 5 The cyclic voltammetry curves of the KOH-C / Te material prepared in Example 1 at different scan rates are shown in FIG. Figure 5 As shown, the shape of the cyclic voltammetry curve remains roughly the same with the increase of scan rate, indicating that Te is uniformly loaded on KOH-C, which is conducive to fast redox reactions and good cycling stability during charge and discharge.
[0097] Figure 6 The KOH-C / Te material prepared in Example 1 was heated to 0.1 Ag. -1Constant current intermittent titration curve under current density and Zn in the charge and discharge process 2+ Diffusion coefficient. Figure 6 The results show that the KOH-C / Te cathode material has an excellent ion diffusion rate, which can be attributed to the uniform loading of Te on KOH-C, no structural collapse during the charge and discharge process, and can be well confined by KOH-C.
[0098] Figure 7 The KOH-C / Te material prepared in Example 1 and the materials in Comparative Examples 1 to 2 were prepared at 1Ag. -1 The long cycle diagram under current density is given by Figure 7 It can be seen that at 1Ag -1 At a current density of 1.3 Å, the KOH-C / Te material in Example 1 still has a capacity of 225.9 mAh g after 1000 cycles. -1 The reversible specific capacity has excellent cycle performance.
[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Te-based composite positive electrode material, characterized in that: The following steps are involved: mixing an alkali activator, activated carbon and water, and subjecting the resulting mixture to a first heat treatment to obtain a heat-treated product; The heat-treated product is mixed with an acid solution and etched to obtain a porous carbon support; The porous carbon support is ground and mixed with Te, and a second heat treatment is performed to obtain a Te-based composite positive electrode material.
2. The preparation method according to claim 1, characterized in that: The alkaline activator includes one or more of KOH, NaOH, KHCO3, NaHCO3 and K2CO3.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the activated carbon to the alkali activator is 1:1-3.
4. The preparation method according to claim 3, characterized in that: The alkali activator, activated carbon and water are mixed for 6 to 12 hours.
5. The preparation method according to claim 4, characterized in that: The temperature of the first heat treatment is 600-800° C., the time is 1-5 hours, and the treatment atmosphere is N 2 .
6. The preparation method according to claim 1, characterized in that: The acid solution includes a hydrochloric acid solution, and the concentration of the acid solution is 1 to 5 mol / L; the etching time is 3 to 12 hours.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the porous carbon support to Te is 0.5 to 3:1; the temperature of the second heat treatment is 450 to 650° C., the time is 3 to 15 hours, and the atmosphere is N2 atmosphere.
8. The Te-based composite positive electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises a porous carbon support and Te particles loaded on the porous carbon support.
9. The Te-based composite cathode material according to claim 8, characterized in that: The porous carbon carrier is in an irregular block shape with an average thickness of 40 μm and a length of 70 μm. The loading amount of Te particles on the porous carbon carrier is 0.5-3 mg / cm 2 .
10. Use of the Te-based composite positive electrode material prepared by the preparation method according to claim 8 or 9 in aqueous zinc ion batteries.